Implementation of the Website-Based Prototyping Method for Marketing Management Information Systems for MSME Products in Pangkep Regency - Cici Damayanti Oki; Lilis Nur Hayati; Amaliah Faradibah (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
This research is motivated by the importance of website-based marketing digitalization to improve the competitiveness of MSMEs in Pangkep Regency, which still face limitations in integrated marketing systems, unstructured product catalog management, and suboptimal online transaction processes. This study aims to develop a website-based marketing management information system for MSME products in Pangkep Regency using the prototyping method and to evaluate its feasibility in terms of functionality, interface design, and ease of use. The research applied an iterative prototyping method, including requirements gathering, initial prototype development, user evaluation, and repeated refinement based on feedback from MSME actors and prospective users. The system was implemented using PHP and MySQL with security measures such as input validation, CSRF tokens, and data sanitization. System testing was conducted through alpha testing for functionality and beta testing using a Likert-scale questionnaire. The results indicate that the developed system successfully meets user needs with functional features and achieves an average score of 4.4 or an index of 89.03%, which falls into the “Excellent” category, showing that the system is highly suitable for use by MSMEs in Pangkep Regency.